Carbon Nanofiber versus Graphene‐Based Stretchable Capacitive Touch Sensors for Artificial Electronic Skin. Issue 2 (27th December 2017) - Cataldi, Pietro; Dussoni, Simeone; Ceseracciu, Luca; Maggiali, Marco; Natale, Lorenzo; Metta, Giorgio; Athanassiou, Athanassia; Bayer, Ilker S.
Abstract: Stretchable capacitive devices are instrumental for new‐generation multifunctional haptic technologies particularly suited for soft robotics and electronic skin applications. A majority of elongating soft electronics still rely on silicone for building devices or sensors by multiple‐step replication. In this study, fabrication of a reliable elongating parallel‐plate capacitive touch sensor, using nitrile rubber gloves as templates, is demonstrated. Spray coating both sides of a rubber piece cut out of a glove with a conductive polymer suspension carrying dispersed carbon nanofibers (CnFs) or graphene nanoplatelets (GnPs) is sufficient for making electrodes with low sheet resistance values (≈10 Ω sq −1 ). The electrodes based on CnFs maintain their conductivity up to 100% elongation whereas the GnPs‐based ones form cracks before 60% elongation. However, both electrodes are reliable under elongation levels associated with human joints motility (≈20%). Strikingly, structural damages due to repeated elongation/recovery cycles could be healed through annealing. Haptic sensing characteristics of a stretchable capacitive device by wrapping it around the fingertip of a robotic hand (ICub) are demonstrated. Tactile forces as low as 0.03 N and as high as 5 N can be easily sensed by the device under elongation or over curvilinear surfaces. Abstract : Enabling cost‐effective technologies for human–robot interactions is crucial for humanoid robotics. Clean room and polydimethylsiloxane‐free fabrication and characterization of durable and stretchable touch sensors based on carbon nanofibers or graphene nanoplatelets by spraying on synthetic rubber gloves are presented. Carbon nanofiber sensors demonstrate superior sensing ability under elongation.